Δ9-THC Intoxication by Cannabidiol-Enriched Cannabis Extract in Two Children with Refractory Epilepsy: Full Remission after Switching to Purified Cannabidiol - Crippa, José A. S.; Crippa, Ana C. S.; Hallak, Jaime E. C.; Martín-Santos, Rocio; Zuardi, Antonio W. (Frontiers in Pharmacology, 2016)
Animal studies and preliminary clinical trials have shown that cannabidiol-enriched extracts may have beneficial effects for children with treatment-resistant epilepsy. However, these compounds are not yet registered as medicines by regulatory agencies. We describe the cases of two children with treatment-resistant epilepsy (Case A with left frontal dysplasia and Case B with Dravet Syndrome) with initial symptom improvement after the introduction of CBD extracts followed by seizure worsening after a short time. The children presented typical signs of intoxication by ∆9-THC (inappropriate laughter, ataxia, reduced attention, and eye redness) after using a cannabidiol-enriched extract. The extract was replaced by the same dose of purified cannabidiol with no ∆9-THC in both cases, which led to improvement in intoxication signs and seizure remission. These cases support pre-clinical and preliminary clinical evidence suggesting that cannabidiol may be effective for some patients with epilepsy. Moreover, the cases highlight the need for randomized clinical trials using high-quality and reliable substances to ascertain the safety and efficacy of cannabinoids as medicines.